21st Century BioLaw: a proposal (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Providing legal rules for life sciences is not an easy task. On the one hand, for instance, scientific results change rapidly and new areas for research are continuously emerging. On the other hand, legislative procedures are time-consuming and the law risks to be always late. Scientific complexity and ethical divisiveness are also uneasy to deal with by political bodies and courts, requiring precise and specific expertise. In the light of the tricky relationship between life sciences and the law, the article recommends three features that are supposed to help the law in efficiently cope with contemporary and future scientific challenges: openness, updateness, attentiveness.
Keywords: Biolaw; Law and life sciences; Health law; Medical law; Anthropocene